Energy transition complexities in rural and remote Indigenous communities: a case study of Poplar Hill First Nation in northern Ontario. Issue 9 (2nd September 2019) - Rakshit, Roopa; Shahi, Chander; Smith, M. A. (Peggy); Cornwell, Adam
ABSTRACT: The First Nation communities in northern Ontario have unique energy-related challenges within an interdisciplinary context, including historical, geographic, cultural, technological, and regulatory. Presently, undergoing an energy systems transition from off-grid to grid-connection and scoping renewable energy options, these remote communities are exhibiting characteristics of complex adaptive system principles. This is exhibited through non-linear interactions and connectedness among agents and components in the emerging energy system. This paper explores these interfaces through a case study of Poplar Hill First Nation, an Independent Power Authority community. The potentials of the complexity science through a community engagement process is used to encode and enhance understanding of the "contextual" complexities in the development of local economies, adapting to technology advancement, and social changes. The findings will help better appreciate the efforts made by Poplar Hill in their transition to self-sufficient systems with deliberations that may provide practical outcomes. This paper reflects on the deeper trajectories of the human elements embedded within the energy transition process. In conclusion, the paper adds to the academic dialogue on energy system transition adaptations in marginalised Indigenous communities in rural and remote locations.